The Jiangnan Arsenal: A Microcosm of Translation and Ideological Transformation in 19th-century China - Lung, Rachel (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2016)
The Jiangnan Arsenal (1865-1912), a publicly-funded bureau dedicated to the production of military equipment in late Qing China (1664-1911), was established in response to China’s painful defeat in the two Opium Wars (1839-1842 and 1856-1860). The Arsenal’s translation department, staffed by a total of fifty Chinese scholars and nine Westerners at different times, was set up in 1868 to translate and publish translations of Western books and treatises on science and technology. It was the first official unit charged with this task. Its stated pragmatic function was to assist the arsenal technicians in their production of weapons, although the translations were also marketed to outsiders. Viewed organically, the Arsenal’s translation department was in many ways a reflection of the ideological and social transformations experienced by China, the Chinese scribes, and the Western oral translators in the late 19th century. A study of this translation institution is therefore relevant to translation studies in three regards. First, the Arsenal’s four decades of existence and its emphasis on the function of translation suggest the importance of translation to imperial China’s pursuit of modernization. Second, the voluminous translated texts published by the Arsenal reflect the collaborative efforts of Western missionaries and Chinese literati, typical in the second half of the 19th century. Third, the Arsenal’s combined role, encompassing both translation and publication, inspired the emergence of journals that published translated articles on Western science, technology, social sciences, and literature at the turn of the 20th century. China’s modernization agenda was significantly advanced by the resulting broader exposure to Western ideas, even though the direct role played by the Arsenal remained rather limited.